1985
DOI: 10.1002/pssa.2210880109
|View full text |Cite
|
Sign up to set email alerts
|

Shape and arrangement of the “hexagonal domain” and distribution of ferroelectric domains in GASH single crystals

Abstract: It is found that GASH single crystals consist of a volume with ferroelectric domain structure and of a “hexagonal domain” usually observed in the central part of samples cleaved perpendicularly to the polar axis. Results are given of scanning electron microscope and electron microscope decoration technique studies of the arrangement of the “hexagonal domain” and of the ferro‐electric domain structure within the bulk of GASH single crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This effect is consistent with results obtained by Szczesniak et al who have found that the dimensions of small circular domains along the polar axis are comparable to those on the polar surface and that small circular domains do not extend through the bulk of the crystal. 3 The size of a large domain on the AFM image ͑about 15 m͒ is smaller than that found in the powder pattern ͑about 50 m͒, apparently due to the inclination of the domain walls from the polar direction. From the AFM topography image the difference in height between opposite domains was found to be about 1 nm.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…This effect is consistent with results obtained by Szczesniak et al who have found that the dimensions of small circular domains along the polar axis are comparable to those on the polar surface and that small circular domains do not extend through the bulk of the crystal. 3 The size of a large domain on the AFM image ͑about 15 m͒ is smaller than that found in the powder pattern ͑about 50 m͒, apparently due to the inclination of the domain walls from the polar direction. From the AFM topography image the difference in height between opposite domains was found to be about 1 nm.…”
Section: Methodsmentioning
confidence: 92%
“…To visualize the domain structures of ferroelectric materials, several methods have been applied, such as polarization microscopy, surface etching, powder decoration, and electron microscopy. [1][2][3][4] Recently the possibility of revealing ferroelectric domains using atomic force microscopy ͑AFM͒ in the micron range has been reported. 5 AFM promises to be a powerful tool for the study of ferroelectric domains providing the nanoscale resolution of domain structure.…”
Section: Introductionmentioning
confidence: 99%